INTERNET OF THINGS PLATFORM BENCHMARK: AN ARTIFICIAL INTELLIGENCE ASSESSMENT (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2024)
The Internet of Things (IoT) represents a transformative technological concept that seamlessly becomes a part of the Internet across all industries. Artificial intelligence (AI) provides IoT with new capabilities used to analyze data in real-time and make informed decisions. There is a wide array of IoT devices with different computational capabilities and AI accelerators that need to be compared. The current paper proposes a comparison between two single-board computers using an existing AI benchmark.
Keywords: Internet of Things; Artificial Intelligence; Hardware; Platforms; Single Board Computer; Benchmark